The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1128/iai.00518-07
|View full text |Cite
|
Sign up to set email alerts
|

SalY of theStreptococcus pyogenesLantibiotic Locus Is Required for Full Virulence and Intracellular Survival in Macrophages

Abstract: Streptococcus pyogenes utilizes numerous mechanisms for evading the host immune response but has only recently been found to survive in the intracellular environment. In this study, we demonstrate the requirement of a putative ABC transporter permease for intracellular survival in macrophages. The highly attenuated S. pyogenes mutant, SalY, was identified from a transposon mutagenesis screen, with over 200-fold attenuation in virulence in a zebrafish invasive-disease model. Sequencing of the region surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 56 publications
(48 reference statements)
2
45
0
Order By: Relevance
“…The expression of emm49, encoding for antiphagocytic M protein, and the expression of the whole sal operon is reduced. SalY is required for full virulence and intracellular survival in macrophages (28). The reduced transcript amounts of both genes leads to a decreased protection against phagocytosis and impaired survival in human media.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of emm49, encoding for antiphagocytic M protein, and the expression of the whole sal operon is reduced. SalY is required for full virulence and intracellular survival in macrophages (28). The reduced transcript amounts of both genes leads to a decreased protection against phagocytosis and impaired survival in human media.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish were inoculated intramuscularly as described above, and histology sections were prepared as reported previously (45). Tissue sections from the zebrafish infected with the reporter construct were stained with an antiserum to detect S. pyogenes (Lee Laboratories, Grayson, GA) at a dilution of 1:500 and incubated for 2 h in a humidified atmosphere at room temperature, after which they were washed with PBS and stained with goat anti-rabbit antibody conjugated to Alexa Fluor 488 (Molecular Probes) at a dilution of 1:2,500 for 30 min.…”
Section: Vol 77 2009 Stm In S Pyogenes 1855mentioning
confidence: 99%
“…These results suggest that the salKR promoter requires tight regulation, indicating the importance of regulated expression of the downstream genes encoding the two-component signaling system salKR. Previous studies demonstrated that the SalKR two-component system is required for the full virulence of pathogenic bacteria like S. suis (29) and S. pyogenes (16).…”
Section: Discussionmentioning
confidence: 99%
“…Genes in the sal locus are important for the full virulence of S. pyogenes strain HSC5 (16). To determine if the identified salKR promoter was affected by host factors, we tested the expression of the salKR promoter (full length with all regulatory sequences) in the wildtype strain in the presence of human serum compared to that in the presence of fetal bovine serum.…”
Section: Promoter Identificationmentioning
confidence: 99%
See 1 more Smart Citation